(untitled) (Journal of Hama University, 2024)
Recently, the interest of using photoelectric pumping systems has been increased; it provides a suitable solution to reduce the costs of water pumping, which used to rely on diesel engines. In this article, we present a modeling and simulation of a photovoltaic pumping system that includes a three-phase squirrel-cage induction motor, an ESP (Electric Submersible Pump) witch operating with a multi-stage centrifugal system, an electronic converter, that converts the continuous voltage coming from the panels into alternative voltage sinusoidal modified. A controller that works according to Perturbing Observe (P&O) algorithm for tracking the maximum power point (MPPT) extracted from the photovoltaic panels. The controller’s output is applied to the (V/f=const) algorithm, which generates control pulses that applied on converter transistor bases, that applied on the induction motor. . Since, the intensity of solar brightness is not constant during the periods of pump operation, but variable in the time, for that a tracking system must existing to tracking the change in the power produced by the panels, which varies according to the intensity of solar brightness, which is represented by the (P&O) algorithm. The simulation results showed the ability of the proposed system to track the maximum and variable power according to the intensity of solar brightness, which gave the best performance of the pumping system during the various stages of its work. The results also showed the importance of working with the voltage regulator (V/f=const) algorithm, as it enabled the pumping system to work at low levels of solar brightness without drawing excessive current, so that the motor driving the pump remains in a safe state.